Nightlife Partnership Policing - (Dis)trust Building Between Bouncers and the Police in the War on Gangs - Thomas Friis Søgaard; Esben Houborg; Sébastien Tutenges (Nordisk Politiforskning)
This article contributes to the research on trust in policing by examining how private security actors (bouncers) experience the police as a partner in informal policing networks emerging as part of the ‘war on bikers and gangs’ in Danish nightlife. While much international research about partnership policing has employed a police perspective and a top-down approach, thus emphasizing organizational ties between policing bodies, this article uses a bottom-up, interactional approach, with a focus on bouncers’ everyday experiences and understandings of partnerships with the police. Our findings show that the formation of informal police-bouncer networks has significantly increased the degree of police influence in private nightlife environments such as bars and nightclubs. Our findings also indicate that inter-agency trust building is crucial to the collaborative willingness and capability of bouncers. However, collaborative relationships are challenged when the police use coercive tactics in their dealings with bouncers and, also, when there is uncertainty about the partition of roles and responsibilities between bouncers and police.